Frequency of Hyponatremia in Patients with Ischemic Stroke Presenting in Neurology Department Chandika Medical College Larkana - Nagina Shaikh, Sameena Majeed, Shahnaz Shah, Muhammad Munwar Ali, Jaysingh, Aijaz Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The World Health Organization describes a stroke as having "rapidly emerging clinical symptoms of localized or generalized impairment of brain function without obvious non-vascular cause1. Hyponatremia is more likely to impede stroke survivors' ability to recover from the condition. Our research evaluated the incidence of hyponatremia in ischemic stroke. Therefore, the precise size of the issue would be evaluated. Objective: To determine the frequency of hyponatremia in patients with ischemic stroke. Material and Methods: The design of this study was a descriptive cross-sectional study. All in patients and out patients coming in Neurology department of Chandka Medical College Hospital Larkana, and the duration of this study was Six months, from 13 October 2020 to 12 April 2021. A total of 107 stroke patients were included in this study. The purpose, risk and benefits of the study were explained to the patient on a prescribed Proforma, Results: A total of 107 Ischemic stroke patients were included in this study. Most of the patients were above 40 years of age. The average age of the patients was 68 years. Out of 107 patients, 70(65%) were male and 37(35%) were female. Frequency of Hyponatremia in patients with ischemic stroke was observed in 24% cases. Rate of developing Hyponatremia was significantly high in age group of 60 to 80 years. Similarly Hyponatremia was significantly high in hypertensives as compared to non-hypertensive Patients (32% vs. 13% p=0.03) . There was no gender predilection seen, Diabetes increased the risk of developing hyponatremia about two folds. (38% versus 20%). Increased BMI, Obesity increased the risk of developing hyponatremia in the setting of ischemic stroke two folds. (36% vs 18%) Conclusion: The prevalence and frequency of post-stroke hyponatremia was found to be considerable. This is especially concerning because hyponatremia has a worse effect than stroke itself on prognosis and death. Keywords: Hyponatremia, Stroke, Ischemic, Hyponatremia, Cerebral Salt Wasting Syndrome, Syndrome of Inappropriate Antidiuretic Hormone Secretion.